(3fTCJgG, JCKjQgG, JWhQgGs - (3hOGO CMeO(B, (3cjcShs ((3YeGf(B:s (3OGQ GdaGQS(B,s, 2002)
(3hdGOI eG jSei EJaGbjI hGTfWf(B- (3JLOjO dEJaGbjI hGTfWf(B- (3EcJTGa GdYhdeI aj CMTGA EJaGbjI hGTfWf(B- (3CcJTGa GdYhdeI hJShjbgG(B- (3EfYcGSGJ EJaGbjI hGTfWf(B- (3JCKjQ GdYhdeI Ydi GdEbJUGOjGJ(B- (3GdJfejI GdEbJUGOjI hGdYhdeI(B- (3bQGAI aj eSJbHd GdYhdeIs
Keywords: (3GdJfejIs; (3GdJfejI GdEbJUGOjIs; (3GdYhdeIs